Nucleolin Overexpression Predicts Patient Prognosis While Providing a Framework for Targeted Therapeutic Intervention in Lung Cancer - Fernandes, Ângela Valério (2022)
Notwithstanding the advances in the treatment of lung cancer with immune checkpoint inhibitors, the high percentage of non-responders supports the development of novel anticancer treatments. Herein, the expression of the onco-target nucleolin in patient-derived pulmonary carcinomas was characterized, along with the assessment of its potential as a therapeutic target. The clinical prognostic value of nucleolin for human pulmonary carcinomas was evaluated through data mining from the Cancer Genome Atlas project and immunohistochemical detection in human samples. Cell surface expression of nucleolin was evaluated by flow cytometry and subcellular fraction Western blotting in lung cancer cell lines. Nucleolin mRNA overexpression correlated with poor overall survival of lung adenocarcinoma cancer patients and further predicted the disease progression of both lung adenocarcinoma and squamous carcinoma. Furthermore, a third of the cases presented extra-nuclear expression, contrasting with the nucleolar pattern in non-malignant tissues. A two- to twelve-fold improvement in cytotoxicity, subsequent to internalization into the lung cancer cell lines of doxorubicin-loaded liposomes functionalized by the nucleolin-binding F3 peptide, was correlated with the nucleolin cell surface levels and the corresponding extent of cell binding. Overall, the results suggested nucleolin overexpression as a poor prognosis predictor and thus a target for therapeutic intervention in lung cancer.